Correlation between Low Temperature Adaptation and Oxidative Stress in Saccharomyces cerevisiae - García-Ríos, Estéfani; Ramos-Alonso, Lucía; Guillamón, José M. (Frontiers in Microbiology, 2016)
Many factors, such as must composition, juice clarification, fermentation temperature or inoculated yeast strain, strongly affect the alcoholic fermentation and aromatic profile of wine. As fermentation temperature is effectively controlled by the wine industry, low-temperature fermentation (10-15 ºC) is becoming more prevalent in order to produce white and “rosé” wines with more pronounced aromatic profiles. Elucidating the response to cold in Saccharomyces cerevisiae is of paramount importance for the selection or genetic improvement of wine strains. Previous research has shown the strong implication of oxidative stress response in adaptation to low temperature during the fermentation process. Here we aimed first to quantify the correlation between recovery after shock with different oxidants and cold, and then to detect the key genes involved in cold adaptation that belong to sulfur assimilation, peroxiredoxins, glutathione-glutaredoxins and thioredoxins pathways. To do so, we analyzed the growth of knockouts from the EUROSCARF collection S. cerevisiae BY4743 strain at low and optimal temperatures. The growth rate of these knockouts, compared with the control, enabled us to identify the genes involved, which were also deleted and validated as key genes in the background of two commercial wine strains with a divergent phenotype in their low-temperature growth. We identified three genes, AHP1, MUP1 and URM1, whose deletion strongly impaired low-temperature growth.